Signalling effects of a large player in a global game of creditor coordination - Tobias Schüle; Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2005)
In case of multiple creditors a coordination problem can arise when the borrowingfirm runs into financial distress. Even if the project's value at maturity is enoughto pay all creditors in full, some creditors may be tempted to foreclose on theirloans. We develop a model of creditor coordination where a large creditor movesbefore a continuum of small creditors, and analyze the signalling effects of the largecreditor's investment decision on the subsequent behavior of the small creditors. Thesignalling effects crucially depend on the relative size of the large creditor and therelative precision of information. We derive conditions under which pure herdingbehavior is to be expected.
urn:nbn:de:bsz:21-opus-20606
Keywords: D82; G12; 330; creditor coordination; global games; Gläubiger; Koordination; Spieltheorie; Signalling; Kreditrisiko; Theorie